2002
DOI: 10.1034/j.1600-0706.2002.960308.x
|View full text |Cite
|
Sign up to set email alerts
|

Foliage color contrasts and adaptive fruit color variation in a bird‐dispersed plant community

Abstract: J. L. 2002. Foliage color contrasts and adaptive fruit color variation in a bird-dispersed plant community. -Oikos 96: 463-469.The color of vertebrate-dispersed fruits has been a source of inquiry for over 150 years, yet the ecological and evolutionary processes responsible for fruit color diversity remain elusive. We tested the hypothesis that fruit color varies temporally, to maximize conspicuousness against seasonal changes in foliage coloration, in a bird-dispersed plant community in western North America.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 31 publications
5
93
1
Order By: Relevance
“…Although inconclusive about selective forces that sharp the dynamics of fruit color polymorphisms and choice by frugivorous birds, our findings corroborated recent studies wherein birds showed preferences by high-over low-contrast fruit signals (e.g. Burns & Dalen, 2002;Schmidt et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although inconclusive about selective forces that sharp the dynamics of fruit color polymorphisms and choice by frugivorous birds, our findings corroborated recent studies wherein birds showed preferences by high-over low-contrast fruit signals (e.g. Burns & Dalen, 2002;Schmidt et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…As birds discriminate between fruit colors, our results suggests that the perception of color by birds was not influenced by use of artificial fruits (see also Alves-Costa & Lopes, 2001). Burns & Dalen (2002) and Schmidt et al (2004) found strong support for the prediction that background foliage coloration influences fruit color preferences by avian frugivores. These authors demonstrated that red fruits had higher removal rates because displayed against contrasting background foliage.…”
Section: Discussionmentioning
confidence: 52%
“…† Flowers and fruits are often displayed against conspicuously coloured, non-green secondary structures, such as coloured infructescences and bracts [19,62]. Do these structures enhance detectability according to the eye of the receiver?…”
Section: Box 2 Future Research Perspectivesmentioning
confidence: 99%
“…Rather, fruit conspicuousness results from spectral contrasts between fruits and their backgrounds (Burns and Dalen 2002;Schmidt et al 2004). Selection by frugivores is therefore likely to favour colours that are perceived as strongly contrasting with their backgrounds, because strong fruitbackground contrasts are more conspicuous and increase the chances that fruits are detected (Schaefer et al 2006).…”
Section: Introductionmentioning
confidence: 99%